Dr. Wolfram Mey’s Stonefly (Insecta: Plecoptera) Collection from Luzon, Philippines: Part I. Perlidae - Pelingen, Arthien Lovell (Zootaxa, 2024)
In this study, the Perlidae stonefly collections of Dr. Wolfram Mey from over 20 years ago have been examined. Neoperla jhoanae sp. nov. from Central Luzon Region and Neoperla nagaensis sp. nov. from Bicol Region are described herein. Additional records and information are also provided on Neoperla jewetti Sivec, 1984, Neoperla recta Banks, 1913, Neoperla pseudorecta Sivec, 1984, Neoperla oculata Banks, 1924, Neoperla nigra Sivec, 1984, Phanoperla bakeri (Banks, 1924), and Phanoperla flaveola (Klapálek, 1910).